2004
DOI: 10.1111/j.1365-2036.2004.02250.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of irritable bowel syndrome in general practice: a striking feature with clinical implications

Abstract: Summary Background : Somatic comorbid symptoms might identify irritable bowel syndrome patients with different aetiologies and needs of treatment. Aims : To measure comorbid symptoms in patients with irritable bowel syndrome in general practice, and to explore characteristics of patients with low, intermediate and high somatic comorbidity. Methods : Prospective study of 208 of 278 consecutive patients with irritable bowel syndrome (Rome II) in nine general practices. Questionnaires assessed 22 comorbid symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
102
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 38 publications
(84 reference statements)
10
102
1
6
Order By: Relevance
“…In addition, nongastrointestinal somatic disorders and psychiatric disorders occur frequently in IBS (4,5). Comorbidity of IBS has been associated with increased use of health resources, impaired quality of life and poor outcome (6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nongastrointestinal somatic disorders and psychiatric disorders occur frequently in IBS (4,5). Comorbidity of IBS has been associated with increased use of health resources, impaired quality of life and poor outcome (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, IBS is also often accompanied by another extra-intestinal symptoms, as asthma and cerebral pain symptoms as primary headache. The pathophysiology mechanisms suggest that IBS patients with one or more somatic comorbitdities might represent a separate sub-group (6,17,20,29,39,42) .…”
Section: Discussionmentioning
confidence: 99%
“…IBS affects 15%-23% of the general population and is the most common reason for patients and generalists to consult gastroenterologists In addition, our data showed that the percentage of IBS diagnosis and PH is in accordance with other studies. IBS affects 15%-23% of the general population and is the most common reason for patients and general practitioners to consult gastroenterologists (6,20,26,29,31,39,42) . Globally, the percentage of adult population with an active headache disorder is 47%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations